Pengaruh Promosi Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian dengan Minat Beli Sebagai Variabel Intervening(Studi Kasus Mahasiswa Universitas Putra Indonesia “YPTK” Padang Khusus Manajemen) - Mutia Riski Syawalni; Emil Salim; Muhammad Pondrinal (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of promotion and consumer trust on purchasing decisions with buying interest as an intervening variable on the Shopee e-commerce platform. The rapid growth of digital commerce in Indonesia has intensified competition among e-commerce platforms, requiring companies to implement effective promotional strategies and build strong consumer trust. This research employed a quantitative approach with a causal associative design. The population consisted of Management students of Universitas Putra Indonesia YPTK Padang class of 2022 who actively use Shopee. A purposive sampling technique was applied, resulting in 100 respondents. Data were collected using questionnaires and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results indicate that promotion and consumer trust have a positive and significant effect on buying interest. Furthermore, promotion, consumer trust, and buying interest significantly influence purchasing decisions. Buying interest is also proven to mediate the effect of promotion and consumer trust on purchasing decisions. These findings suggest that strengthening promotional programs and maintaining consumer trust can increase buying interest and ultimately encourage purchasing decisions on Shopee.